Isolation and quantitative HPLC-PDA analysis of lupeol in phytopharmaceutical intermediate products from Vernonanthura ferruginea (Less.) H. Rob. - Ezequiane Machado Silva Oliveira; Sabrine Lemes Freitas; Frederico Severino Martins; Renê Oliveira Couto; Mariana Viana Pinto; José Realino Paula; Edemilson Cardoso Conceição; Maria Teresa Freitas Bara (Química Nova, 2012)
Prior to obtain a standardized dried extract from V. ferruginea, lupeol was first time isolated from leaves and used as chemical maker. An analytical method using HPLC-PDA for lupeol determination in V. ferruginea intermediate products was developed using a C8 reverse-phase column, acetonitrile-acetic acid (99.99:0.01, v/v) as mobile phase at 0.8 mL min-1, oven temperature at 23-25 ºC, sample injection volume at 30 µL and detection at 210 nm. The method presented linearity from 10 to 160 µg mL-1, accuracy, precision, robustness and suitable sensitivity proving to be a useful tool to the obtainment process of lupeol standardized dried extracts of V. ferruginea.